The Role of Broccoli ( Brassica oleracea ) in Treatment For Induced Polycystic ovary syndrome in Albino rats ( Rattus norvegicus ) - Nahla J. AL-Shahery; Roqaya A. Salih (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The goal of present study was to investigate the benefits of broccoli (as antiandrogenic plant) in protection and treatment for reproductive hormonal and metabolic disturbance, which combined with polycystic ovarian syndrome (PCOS). The PCOS model was introduced by injecting subcutaneously prepubertal female rats at 21 days old with Letrozole for 39 days, and divided into 6 groups (8 rats each ) as follows: